NUHS-MD anderson pathology update Singapore 27-29 Oktober 2011 - Seng, Ch'ng Ewe (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Objectives: In vitro and in vivo studies have shown involvement of Sema4D, a Class IV semaphorin, in tumor progression. This study aims to characterize the expression of Sema4D in human invasive breast ductal carcinoma and to evaluate its association with pertinent clinicopathological parameters. Materials and Methods: Expression of Sema4D in 94 patients diagnosed of invasive ductal carcinoma was evaluated immunohistochemically on paraffin-embedded sections. Three best-stained hotspots per case were selected for evaluation employing an intensity distribution score (IDS), a modified Hscore system. Expression was categorized as high or low using median score as cutoff for statistical analysis. Results: Carcinoma cells variably expressed Sema4D. Eighty percent (228/282) of the hotspots coincided with the tumor front. The distribution of IDS of Sema4D expression was skewed (mean 230.32, standard deviation 52.31). No significant association between the levels of expression of Sema4D and age, race, tumor size, tumor grade, number of lymph node metastases, estrogen or progesterone receptor status was observed (p> 0.05). High expression of Sema4D was significantly associated with higher expression of the oncogene, Her-2 (p =0.037). Conclusion: Invasive ductal carcinomas mostly express Sema4D at the tumor front. Sema4D might have prognostic significance as its expression significantly associates with Her·2 expression.